2015
DOI: 10.1002/ajmg.b.32283
|View full text |Cite
|
Sign up to set email alerts
|

An association between a dopamine transporter gene (SLC6A3) haplotype and ADHD symptom measures in nonclinical adults

Abstract: Previous genetic studies have postulated that attention deficit hyperactivity disorder (ADHD) should be regarded as the extreme end of a set of behavioural traits that can be continuously measured in the general population. The current study adopted a quantitative trait approach to examine the relationship between dopamine gene variants and self-reported ADHD symptoms in 517 nonclinical adults. Although genetic associations with variants of both the dopamine transporter (DAT1; SLC6A3) and D4 receptor (DRD4) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 86 publications
0
11
0
1
Order By: Relevance
“…Maternal inflammation has been previously shown to cause offspring deficits in latent and prepulse inhibition, along with decreased social and exploratory behavior (Smith et al, 2007), which are associated with dopamine dysfunction and mental health disorders such as schizophrenia and ASD. The increased inflammation that accompanies maternal HFD consumption likely impacts the dopaminergic system of offspring, causing increased risk of psychopathology as changes in the dopaminergic system are associated with disorders such as ASD(Bowton et al, 2014; Hamilton et al, 2015; Staal, 2014), ADHD (Hasler et al, 2015; Pan et al, 2015; Tong et al, 2015), schizophrenia (Howes et al, 2015; Slifstein et al, 2015; Sumiyoshi et al, 2014), anxiety (Agius et al, 2014; Lee et al, 2015), and depression (Clausius et al, 2009; Dunlop and Nemeroff, 2007). …”
Section: Mechanisms By Which Maternal High-fat Diet Consumption mentioning
confidence: 99%
“…Maternal inflammation has been previously shown to cause offspring deficits in latent and prepulse inhibition, along with decreased social and exploratory behavior (Smith et al, 2007), which are associated with dopamine dysfunction and mental health disorders such as schizophrenia and ASD. The increased inflammation that accompanies maternal HFD consumption likely impacts the dopaminergic system of offspring, causing increased risk of psychopathology as changes in the dopaminergic system are associated with disorders such as ASD(Bowton et al, 2014; Hamilton et al, 2015; Staal, 2014), ADHD (Hasler et al, 2015; Pan et al, 2015; Tong et al, 2015), schizophrenia (Howes et al, 2015; Slifstein et al, 2015; Sumiyoshi et al, 2014), anxiety (Agius et al, 2014; Lee et al, 2015), and depression (Clausius et al, 2009; Dunlop and Nemeroff, 2007). …”
Section: Mechanisms By Which Maternal High-fat Diet Consumption mentioning
confidence: 99%
“…The dopaminergic system is involved in the pathophysiology of ADHD and DAT has been associated with the condition [Swanson et al, ], with mouse models that homozygously knockout DAT (DAT‐KO) displaying severe hyperactivity [Giros et al, ; Spielewoy et al, ; Pogorelov et al, ]. Because the most severe phenotypes occur when both alleles are deleted, individuals that are hemizygous for SLC6A3 may be uniquely sensitive to the detrimental effects of other ADHD‐susceptibility alleles that have been reported for this gene [Tong et al, ].…”
Section: Dosage Sensitive Genes: Conditionally Haploinsufficientmentioning
confidence: 99%
“…More recent studies suggested that the 10-repeat allele might increase ADHD risk in children particularly in the context of a haplotype with the 6-repeat allele of another VNTR in intron 8 of the gene (Asherson et al 2007 ; Brookes et al 2008 ). A recent study also found an association between this 10-6 haplotype and ADHD symptom measures in nonclinical adults (Tong et al 2015 ), but association studies in clinical samples of adults with ADHD could not confirm this relationship (BrĂŒggemann et al 2007 ) and reported an association of the 9-6 haplotype with adult ADHD (Franke et al 2008 , 2010 ). Together, these findings suggest a role for DAT1 in modulating the ADHD phenotype across the lifespan, with different associations depending on age and diagnostic status.…”
Section: Introductionmentioning
confidence: 99%